The Critical Analysis of Hiwar in Madrasah Ibtidaiyyah Textbook based on Core Competencies in the Republic of Indonesia - Suci Ramadhanti Febriani; Kddour Guettaoui Bedra; Rahmawati Rahmawati (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2022)
The Arabic teaching materials require adjustments to the core competencies listed in the Decrees of the Minister of Religious Affairs (Keputusan Menteri Agama/KMA) Number 183 and 184. Based on the previous statement, this study aims to examine hiwar teaching materials based on the KMA curriculum Number 183 and 184 in 2019. This research adopts a qualitative approach based on in-depth text analysis. This study